Autophagy in Cancer Therapy - Fulda, Simone (Frontiers in Oncology, 2017)
Autophagy represents a catabolic program involved in the degradation of cellular components via lysosomes. It serves to mitigate cellular stress and to provide metabolic precursors especially upon starvation. Thereby, autophagy can support the survival of cancer cells. In addition, there is now convincing evidence showing that under certain conditions autophagy can also foster cell death. This dual function of autophagy is also relevant upon anticancer treatment, as many chemotherapeutic agents engage autophagy. A better understanding of the molecular mechanisms that are critical for mediating autophagic cell death in cancer cells will be instrumental to selectively interfere with this cellular program in order to increase the cancer cell’s response to cytotoxic drugs. This review illustrates how anticancer drug-induced autophagy is involved in mediating cell death.